(untitled) (Innovaciones Educativas, 2025)
Introduction: Incentive scholarships constitute a crucial element, although under researched, of student support programs in higher education, especially in distance education. This study analyzes the impact of the Student Training Program with Scholarship at the State Distance University (UNED) of Costa Rica on student retention, academic performance, and graduation. Methodology: A comparative study was conducted between two groups of students during the 2015-2020 period: those who participated in the incentive scholarship program for at least three quadrimesters (n=531) and a control group without scholarships (n=536). Indicators of retention, academic performance, and graduation were assessed using statistical bivariate tests. Results: Students who received incentive scholarship showed better indicators compared to the control group: lower study interruption rate (12% vs. 54%), higher grades in average (7,45 vs. 5,48), and higher graduation rate at the undergraduate level (38% vs. 14%). Statistical tests confirmed significant and positive associations between the incentive scholarship and the three assessed indicators. Conclusions: The Student Training Program with Scholarship has a positive impact on the academic trajectory of the UNED student population. The results highlight the importance of incentive scholarships as a strategy to promote student retention and academic performance in distance higher education.